The Impact of Diabetes Mellitus on the Second Primary Malignancies in Colorectal Cancer Patients - Halamkova, Jana; Kazda, Tomas; Pehalova, Lucie; Gonec, Roman; Kozakova, Sarka; Bohovicova, Lucia; Slaby, Ondrej; Demlova, Regina; Svoboda, Marek; Kiss, Igor (Frontiers in Oncology, 2021)
Introduction: All colorectal cancer (CRC) survivors have an increased risk of developing second primary malignancies (SPMs). The association between diabetes mellitus (DM) and the risk of cancer is well known. However, the role of DM and its therapy in the development of SPMs in CRC patients is not well described. Methods: In this single-institutional retrospective analysis we identified 1174 colorectal carcinoma patients, median follow-up 10.1 years, (median age 63 years, 724 men). A SPM was diagnosed in 234 (20%) patients, DM in 183 (15%) patients. SPMs developed due to hereditary cancer syndrome were excluded. Tumours are considered multiple primary malignancies if arising in different sites and/or are of a different histology or morphology group. Results: DM was diagnosed in 22.6% of those with SPM vs. in 13.8% of those without SPM (p=0.001). The most common types of SPMs in DM patients were other CRC, kidney, lung, bladder and nonmelanoma skin cancer, but only carcinoma of the liver and bile duct tracts was significantly more common than in the group without DM. Although breast cancer is the second most common in the group with DM, its incidence is lower than in the group without DM, as well as prostate cancer. A significantly higher incidence of SPMs was found in older CRC patients (≥ 65 years) and in those with lower stage colon cancer and DM. No significant difference in DM treatment between those with and without a SPM was observed including analysis of type of insulin. Conclusion: CRC patients with diabetes mellitus, especially those with older age, and early stages of colon cancer, should be screened for second primary malignancies more often than the standard population. Patients without DM have longer survival. According to the occurrence of the most common second malignancies, a clinical examination, blood count, and ultrasound of the abdomen is appropriate, together with standard breast and colorectal cancer screening, and lung cancer screening under certain conditions, and should be recommended in CRC survivors especially in patients with intercurrent DM, however the necessary frequency of screening remains unclear.